Evaluating the factor structure, item analyses, and internal consistency of hospital anxiety and depression scale in Iranian infertile patients - Payam Amini; Saman Maroufizadeh; Reza Omani Samani (Shahid Sadoughi University of Medical Sciences, 2017)
Background: The hospital anxiety and depression scale (HADS) is a common screening tool designed to measure the level of anxiety and depression in different factor structures and has been extensively used in non-psychiatric populations and individuals experiencing fertility problems. Objective: The aims of this study were to evaluate the factor structure, item analyses, and internal consistency of HADS in Iranian infertile patients. Materials and Methods: This cross-sectional study included 651 infertile patients (248 men and 403 women) referred to a referral infertility Center in Tehran, Iran between January 2014 and January 2015. Confirmatory factor analysis was used to determine the underlying factor structure of the HADS among one, two, and threefactor models. Several goodness of fit indices were utilized such as comparative, normed and goodness of fit indices, Akaike information criterion, and the root mean squared error of approximation. In addition to HADS, the Satisfaction with Life Scale questionnaires as well as demographic and clinical information were administered to all patients. Results: The goodness of fit indices through CFAs exposed that three and onefactor model provided the best and worst fit to the total, male and female datasets compared to the other factor structure models for the infertile patients. The Cronbach's alpha for anxiety and depression subscales were 0.866 and 0.753 respectively. The HADS subscales significantly correlated with SWLS, indicating an acceptable convergent validity. Conclusion: The HADS was found to be a three-factor structure screening instrument in the field of infertility.